Measuring economic growth using production possibility frontier under Harrod neutrality. (18th April 2018) - Mert, Merter
Economic growth occurs when an economy's production at the full employment level increases. Increase in the production at the full employment level is shown by an outward shift of production possibility frontier (PPF). The aim of this study is to measure capacity growth of an economy by utilizing equation of the PPF. The present study takes into account a bowed-out (concave to the origin) PPF in order to measure economic growth. Thus, at first, concavity conditions are obtained. Besides, the study augments Cobb–Douglas production function by assuming the nature of technological progress as Harrod neutral. For this reason, concavity conditions are obtained assuming Harrod neutrality. The first result of the article documents that there are conditions in order to guarantee positive economic growth. The second result indicates that growth of productive capacity depends on (i) rate of growth of labour, (ii) rate of growth of level of technology (rate of growth of the labour productivity) and (iii) elasticity parameters, under specific conditions. Based on these results, our study formally proves that the long-term or natural or potential rate of growth is determined by rate of growth of effective labour.